Alternative pain management via endocannabinoids in the time of the opioid epidemic: Peripheral neuromodulation and pharmacological interventions. (21st January 2022) - Lee, Ming Tatt; Mackie, Ken; Chiou, Lih‐Chu
Abstract : The use of opioids in pain management is hampered by the emergence of analgesic tolerance, which leads to increased dosing and side effects, both of which have contributed to the opioid epidemic. One promising potential approach to limit opioid analgesic tolerance is activating the endocannabinoid system in the CNS, via activation of CB1 receptors in the descending pain inhibitory pathway. In this review, we first discuss preclinical and clinical evidence revealing the potential of pharmacological activation of CB1 receptors in modulating opioid tolerance, including activation by phytocannabinoids, synthetic CB1 receptor agonists, endocannabinoid degradation enzyme inhibitors, and recently discovered positive allosteric modulators of CB1 receptors. On the other hand, as non‐pharmacological pain relief is advocated by the US‐NIH to combat the opioid epidemic, we also discuss contributions of peripheral neuromodulation, involving the electrostimulation of peripheral nerves, in addressing chronic pain and opioid tolerance. The involvement of supraspinal endocannabinoid systems in peripheral neuromodulation‐induced analgesia is also discussed. LINKED ARTICLES: This article is part of a themed issue on Advances in Opioid Pharmacology at the Time of the Opioid Epidemic. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v180.7/issuetoc